Functional, Non-Clonal IgMa-Restricted B Cell Receptor Interactions with the HIV-1 Envelope gp41 Membrane Proximal External Region - Verkoczy, Laurent; Moody, M. Anthony; Holl, T. Matt; Bouton-Verville, Hilary; Scearce, Richard M.; Hutchinson, Jennifer; Alam, S. Munir; Kelsoe, Garnett; Haynes, Barton F. (PloS one, 2009)
The membrane proximal external region (MPER) of HIV-1 gp41 has several features that make it an attractive antibody-based vaccine target, but eliciting an effective gp41 MPER-specific protective antibody response remains elusive. One fundamental issue is whether the failure to make gp41 MPER-specific broadly neutralizing antibodies like 2F5 and 4E10 is due to structural constraints with the gp41 MPER, or alternatively, if gp41 MPER epitope-specific B cells are lost to immunological tolerance. An equally important question is how B cells interact with, and respond to, the gp41 MPER epitope, including whether they engage this epitope in a non-canonical manner i.e., by non-paratopic recognition via B cell receptors (BCR). To begin understanding how B cells engage the gp41 MPER, we characterized B cell-gp41 MPER interactions in BALB/c and C57BL/6 mice. Surprisingly, we found that a significant (approximately 7%) fraction of splenic B cells from BALB/c, but not C57BL/6 mice, bound the gp41 MPER via their BCRs. This strain-specific binding was concentrated in IgM(hi) subsets, including marginal zone and peritoneal B1 B cells, and correlated with enriched fractions (approximately 15%) of gp41 MPER-specific IgM secreted by in vitro-activated splenic B cells. Analysis of Igh(a) (BALB/c) and Igh(b) (C57BL/6) congenic mice demonstrated that gp41 MPER binding was controlled by determinants of the Igh(a) locus. Mapping of MPER gp41 interactions with IgM(a) identified MPER residues distinct from those to which mAb 2F5 binds and demonstrated the requirement of Fc C(H) regions. Importantly, gp41 MPER ligation produced detectable BCR-proximal signaling events, suggesting that interactions between gp41 MPER and IgM(a) determinants may elicit partial B cell activation. These data suggest that low avidity, non-paratopic interactions between the gp41 MPER and membrane Ig on naïve B cells may interfere with or divert bnAb responses.